Climate change adaptation in urban areas. Case study for the Tineretului area in Bucharest. (2017) - Stancu, Mihai; Cheveresan, Maria; Zaharia, Valentin; Poienariu, Tudor
Abstract: Urban drainage systems are loaded directly by precipitation and snow melting processes and their hydraulic capacity must be sufficient to be able to convey the water volumes without discharging to the surface causing flooding. Urban drainage systems are also affected by the groundwater levels by increasing the water volumes that are transported through the system. The receiving waters may also be affected by climate change in terms of higher water levels which can have significant back water effects and reduced outlet discharge capacity in the urban drainage system [1]. Climate change may lead to an increased groundwater level which affects the urban drainage system by additional volumes infiltrated into the sewer from the underground. This infiltration may lead to a reduction of the hydraulic capacity of the collection system and in increased pressure over the wastewater treatment plant. The increased groundwater level can affect the percolation process and may lead to local flooding and reduced hydraulic capacity in the urban drainage system [1].